2021
DOI: 10.1177/0143831x211017216
|View full text |Cite
|
Sign up to set email alerts
|

Turnover intentions, training and motivations among Australian union staff

Abstract: Staff loss and demotivation can be costly for unions. In this article the authors investigate factors influencing expected voluntary turnover, that is Intention to Leave (ITL), of union employees by conducting an online survey of 160 staff in three Australian unions. Moderated multiple regression analyses revealed that perceived organisational support, shortcomings in training and unmet intrinsic needs predicted ITL, after controlling for burnout, labour market mobility and intrinsic motivations. Critically, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 88 publications
(161 reference statements)
0
1
0
Order By: Relevance
“…Even though the incentives are significant, the increased workload can also cause turnover intensity [19,65] Therefore, the decision-makers of the ministries direct their personnel policy and strategy to focus more on the implementation of fairness and equality to employees through performance evaluations, salary increases, bonuses, and gifts, and in terms of rewards and recognition HRM must increase employee satisfaction by increasing their willingness and desire to contribute more and maximize work contribution by assigning appropriate rewards and rewards DOI 10.18502/kss.v9i14.16146 through incentives to motivate them and increase their job satisfaction. In addition, the indirect relationship between employee engagement also acts as a mediating bridge between life satisfaction and work motivation [66,67]. It was found that the most important factors are considered as a form of employee commitment.…”
Section: Hypothesis Examiningmentioning
confidence: 99%
“…Even though the incentives are significant, the increased workload can also cause turnover intensity [19,65] Therefore, the decision-makers of the ministries direct their personnel policy and strategy to focus more on the implementation of fairness and equality to employees through performance evaluations, salary increases, bonuses, and gifts, and in terms of rewards and recognition HRM must increase employee satisfaction by increasing their willingness and desire to contribute more and maximize work contribution by assigning appropriate rewards and rewards DOI 10.18502/kss.v9i14.16146 through incentives to motivate them and increase their job satisfaction. In addition, the indirect relationship between employee engagement also acts as a mediating bridge between life satisfaction and work motivation [66,67]. It was found that the most important factors are considered as a form of employee commitment.…”
Section: Hypothesis Examiningmentioning
confidence: 99%